2009
DOI: 10.1007/978-3-642-04027-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Realm of Systematic Proof Theory

Abstract: Abstract. This paper is part of a general project of developing a systematic and algebraic proof theory for nonclassical logics. Generalizing our previous work on intuitionistic-substructural axioms and singleconclusion (hyper)sequent calculi, we define a hierarchy on Hilbert axioms in the language of classical linear logic without exponentials. We then give a systematic procedure to transform axioms up to the level P 3 of the hierarchy into inference rules in multiple-conclusion (hyper)sequent calculi, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Above, we use the notation ∧ and ∨ to reflect that in a classical calculus, the connectives conjunction and disjunction satisfy the respective properties. Our recipe abstracts and reformulates for display calculi the procedure in [5,6], defined for (hyper)sequent calculi and substructural logics. To transform axioms into structural rules we use: (1) the invertible logical rules of C and (2) the display calculus formulation, below, of the so-called Ackermann's lemma that allows a formula in a rule to switch sides of the sequent moving from conclusion to premises.…”
Section: Definition 4 (Amenable Calculus)mentioning
confidence: 99%
See 2 more Smart Citations
“…Above, we use the notation ∧ and ∨ to reflect that in a classical calculus, the connectives conjunction and disjunction satisfy the respective properties. Our recipe abstracts and reformulates for display calculi the procedure in [5,6], defined for (hyper)sequent calculi and substructural logics. To transform axioms into structural rules we use: (1) the invertible logical rules of C and (2) the display calculus formulation, below, of the so-called Ackermann's lemma that allows a formula in a rule to switch sides of the sequent moving from conclusion to premises.…”
Section: Definition 4 (Amenable Calculus)mentioning
confidence: 99%
“…[5,6,16,14,15,11] introduce methods to extract rules out of suitable Hilbert axioms. More precisely [5,6] generate sequent and hypersequent rules, [11] nested sequent rules, [15] sequent rules for certain modal axioms, and [16] labelled rules; finally [14] transforms suitable modal and tense axioms (called primitive tense axioms) into structural rules for the display calculus. [14] also provides a characterisation as it is shown that each such rule added to the base system is equivalent to the extension of the logic by primitive tense axioms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, these questions have been intensely investigated in the context of various proof-theoretic formalisms (cf. [39,6,10,32,7,36,34,38,35]). Perhaps the first paper in this line of research is [33], which addresses these questions in the setting of display calculi for basic normal modal and tense logic.…”
Section: Tools Of Unified Correspondence Theorymentioning
confidence: 99%
“…9 ALBA is the acronym of Ackermann Lemma Based Algorithm. 10 Throughout the paper, order-types will be typically associated with arrays of variables p := (p 1 , . .…”
Section: Definitionmentioning
confidence: 99%